A summer blizzard in Sydney : based on Abdul Samad Amjah's true story - 501526 Abdul Samad Amjah; Ishak Salleh; Daud Awang (Batu Berendam, Melaka, Malaysia : Malaysian Institute of Historical and Patriotism Studies, 2004)
PSZJBL